Resistensi Warga di Bantaran Ciliwung terhadap Rencana Penggusuran oleh Pemerintah - Pramudita Pramudita; Budhi Gunawan; Selly Riawanty (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2020)
This paper focuses on the topic of normalization which apparently is not always acceptable to the community, it raises resistance to the community. In this study entitled "Citizens Resistance in Ciliwung River Against Plans for Eviction by the Government ", the researcher looked at how the resistance patterns carried out by the people in the Low Land area. The method used in this research is in-depth interviews. This research is descriptive-qualitative in nature. The results of this study indicate that resistance by residents in the region is closed and categorized as closed resistance. In hidden transcripts it appears that citizens obey the government by reporting the area of land and buildings and agreeing on the area of land and buildings that have been measured by officials from the National Land Agency, but in public transcripts the citizens clandestinely continue to show disapproval of the normalization program from the government